Fundamental Analysis for Strategic Performance Evaluation in Indofood and Mayora - A. Reski Almaida Dg Macenning; Rahmat Burhamzah (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze and compare the financial performance of PT Indofood CBP Sukses Makmur Tbk (ICBP) and PT Mayora Indah Tbk (MYOR), two leading companies in the food and beverage subsector listed on the Indonesia Stock Exchange. This research employs a quantitative approach with a descriptive comparative method through financial ratio analysis, including Earnings Per Share (EPS), Price Earnings Ratio (PER), Price to Book Value (PBV), Return on Equity (ROE), Debt to Equity Ratio (DER), and Dividend Yield (DY) for the 2019–2023 period. The study uses secondary data obtained from annual financial reports and the official website of the Indonesia Stock Exchange. The results indicate that PT Indofood CBP demonstrates more stable and efficient financial performance than PT Mayora Indah, particularly in profitability and capital efficiency ratios. Meanwhile, PT Mayora Indah shows promising growth potential but tends to experience fluctuations due to high operating costs and aggressive expansion strategies. The managerial implication emphasizes the importance of balancing operational efficiency and growth strategies to enhance corporate value and long-term investment attractiveness.